2021
DOI: 10.1029/2021jg006319
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Geochemical and Microbial Variation Across Discrete Depth Intervals in a Peridotite Aquifer Assessed Using a Packer System in the Samail Ophiolite, Oman

Abstract: The potential for molecular hydrogen ( 2 H ) generated via serpentinization to fuel subsurface microbial ecosystems independent from photosynthesis has prompted biogeochemical investigations of serpentinization-influenced fluids. However, investigations typically sample via surface seeps or open-borehole pumping, which can mix chemically distinct waters from different depths. Depthindiscriminate sampling methods could thus hinder understanding of the spatial controls on nutrient availability for microbial life… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 162 publications
(543 reference statements)
6
64
0
Order By: Relevance
“…Recent work utilizes next generation DNA sequencing for taxonomic and functional classification of borehole fluids in combination with other techniques such as microcosm or enrichment based experiments ( Crespo-Medina et al, 2014 ; Meyer-Dombard et al, 2018 ; Fones et al, 2021 ; Glombitza et al, 2021 ), stable isotope analyses ( Nothaft et al, 2021a , b ), radioisotope labeling ( Fones et al, 2021 ; Glombitza et al, 2021 ; Templeton et al, 2021 ), and ecological/hydrological modeling ( Putman et al, 2021 ). Transcriptomic and single cell genomics studies have also shown mechanisms of adaptation of microbial life to serpentinizing environments ( Fones et al, 2019 , 2021 ; Merino et al, 2020 ; Kraus et al, 2021 ).…”
Section: Exploring the Terrestrial Deep Biospherementioning
confidence: 99%
See 4 more Smart Citations
“…Recent work utilizes next generation DNA sequencing for taxonomic and functional classification of borehole fluids in combination with other techniques such as microcosm or enrichment based experiments ( Crespo-Medina et al, 2014 ; Meyer-Dombard et al, 2018 ; Fones et al, 2021 ; Glombitza et al, 2021 ), stable isotope analyses ( Nothaft et al, 2021a , b ), radioisotope labeling ( Fones et al, 2021 ; Glombitza et al, 2021 ; Templeton et al, 2021 ), and ecological/hydrological modeling ( Putman et al, 2021 ). Transcriptomic and single cell genomics studies have also shown mechanisms of adaptation of microbial life to serpentinizing environments ( Fones et al, 2019 , 2021 ; Merino et al, 2020 ; Kraus et al, 2021 ).…”
Section: Exploring the Terrestrial Deep Biospherementioning
confidence: 99%
“…Both host rock composition and hydrologic context influence microbial community composition in subsurface serpentinizing systems, and recent work at the MBO in Oman highlights this concept ( Miller et al, 2016 ; Rempfert et al, 2017 ; Fones et al, 2019 ; Kraus et al, 2021 ; Nothaft et al, 2021a ). The Samail Ophiolite is composed of mafic gabbros and ultramafic peridotites, mainly harzburgite, both presumed to be undergoing active serpentinization, which fuel distinct microbial communities ( Neal and Stanger, 1983 ; Miller et al, 2016 ; Rempfert et al, 2017 ; Fones et al, 2019 ; Nothaft et al, 2021a ).…”
Section: Exploring the Terrestrial Deep Biospherementioning
confidence: 99%
See 3 more Smart Citations